2021
DOI: 10.1038/s41586-021-03584-2
|View full text |Cite
|
Sign up to set email alerts
|

Operando optical tracking of single-particle ion dynamics in batteries

Abstract: Key to advancing lithium-ion battery technology, and in particular fast charging capabilities, is our ability to follow and understand the dynamic processes occurring in operating materials under realistic conditions, in real time, and on the nano-to mesoscale. Currently, operando imaging of lithium-ion dynamics requires sophisticated synchrotron X-ray or electron microscopy techniques, which do not lend themselves to high-throughput material screening. This limits rapid and rational materials improvements. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
158
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 57 publications
9
158
1
1
Order By: Relevance
“…Another method for investigating lithium deposition during cycling is insitu observation using special cell holders. Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method for investigating lithium deposition during cycling is insitu observation using special cell holders. Insitu observations in the ECC-Opto Stud, manufactured by EL-Cells GmbH (Hamburg, Germany), on battery cells were made in [26][27][28][29][30][31][32][33] using Raman spectroscopy, X-ray diffraction (XRD) and optical analytics. Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging.…”
Section: Future Workmentioning
confidence: 99%
“…Observations were made using Raman spectroscopy [27,31,32] and XRD [26,28,33] to observe changes in electrodes and SEI during aging. Merryweather et al [29] used the above-mentioned cell housing for optical interferometric scattering measurements to detect single-particle ion dynamics, and Rittweger et al [30] observed the reflectivity of cathodes during charge and discharge.…”
Section: Future Workmentioning
confidence: 99%
“…The urgent demand for high-performance energy storage devices has triggered a new upsurge in research on high-energy-density lithium-ion batteries. 1–3 Nevertheless, due to the potential safety hazards and low theoretical energy densities of conventional lithium-ion batteries consisting of flammable liquid electrolyte (LE) and graphite anodes, researchers have begun to pursue superior alternatives. 4–6 Combining a non-volatile and non-inflammable solid electrolyte with Li metal anodes that have high capacity and low electrochemical potential provides a feasible solution.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] One of the most common strategies to investigate electrode performance is the utilization of galvanostatic cycling. [8][9][10] In each charge/discharge step, a constant current is applied until a designed potential is reached. The C-rate is widely used to describe the discharge/ charge rate and is defined as the current at which a cell can be fully charged or discharged in one hour.…”
Section: Introductionmentioning
confidence: 99%